α10: A determinant of nicotinic cholinergic receptor function in mammalian vestibular and cochlear mechanosensory hair cells - Elgoyhen, Ana Belen (2001)
We report the cloning and characterization of rat α10, a previously unidentified member of the nicotinic acetylcholine receptor (nAChR) subunit gene family. The protein encoded by the α10 nAChR subunit gene is most similar to the rat α9 nAChR, and both α9 and α10 subunit genes are transcribed in adult rat mechanosensory hair cells. Injection of Xenopus laevis oocytes with α10 cRNA alone or in pairwise combinations with either α2-α6 or β2-β4 subunit cRNAs yielded no detectable ACh-gated currents. However, coinjection of α9 and α10 cRNAs resulted in the appearance of an unusual nAChR subtype. Compared with homomeric α9 channels, the α9α10 nAChR subtype displays faster and more extensive agonist-mediated desensitization, a distinct current-voltage relationship, and a biphasic response to changes in extracellular Ca2+ ions. The pharmacological profiles of homomeric α9 and heteromeric α9α10 nAChRs are essentially indistinguishable and closely resemble those reported for endogenous cholinergic eceptors found in vertebrate hair cells. Our data suggest that efferent modulation of hair cell function occurs, at least in part, through heteromeric nAChRs assembled from both α9 and α10 subunits.